Meningkatkan Kesadaran akan Bahaya Pernikahan Dini pada Remaja di Pedesaan melalui Teknik Sosialisasi di SMP PGRI 1 Ngantang - Ayu Shafira Puspitasari; Ashri Shabrina Afrah (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Marriage is the right of every human being. Human instinct to continue civilization. Marriage is the key word for the development of a nation's civilization. Marriage becomes the foundation for better social engineering (Julianto, 2015). Early marriage is a serious case in Indonesia. Early marriage is a social phenomenon that occurs in many regions. The phenomenon of early marriage is like an iceberg phenomenon that only appears a small part on the surface, very little exposed in the public sphere, but in fact it occurs so much among the wider community (Rifiani, 2011). This phenomenon is motivated by several factors such as economic factors, education, customs / culture, religion and because of pregnancy out of wedlock. The impact obtained after early marriage is mostly very detrimental to the perpetrators, such as stress, depression, social conditions such as increasing levels of poverty, the population in Indonesia is increasing, and the impact on health such as pregnant women in adolescence are vulnerable to anemia, babies born to adolescent mothers are at risk of prematurity and low birthweight, babies born to mothers under 20 years old are at risk of malnutrition and stunting, and the risk of dying during childbirth is higher and much more. This community service activity aims to provide proper socialization for adolescents, at which age early marriage often occurs. The method used in this socialization is to use the lecture method, where the speaker delivers the material directly with power point slides. Before and after socialization, the speaker gave questionnaires to students of SMP PGRI 1 Ngantang. This service activity is carried out to provide insight / knowledge to students about early marriage and its harmful effects, as well as preventive ways that can be done to prevent early marriage